Determinants and Dimensions of Customer Switching Behavior – A Systematic Review - KUMAR, N. ARUN; S., DR. GIRISH (The journal of contemporary issues in business and government, 2021)
Switching behavior alludes to customers relinquishing or abandoning an item because of disenchantment from the services provided, which urges him/her to switch from the existing provider of goods/services, to its competitor offering the same commodity. In lieu of understanding and measuring the impact of customer switching behavior and its impact in the market, a systematic review has been attempted to examine the findings of the existing literature available in the domain, theories and postulations, including factors, which are inherent to specific industries across the market and suppositions, which are prevalent in general. This research is driven to uncover means to identify and recognize ways, whereby industries can prevent attrition, and retain customers . The study, however, revealed that customer switching behavior is rampant and prevalent across industries and companies including Banking and Insurance Sectors, Fast-Moving Consumer Goods Sector (FMCG), and the Telecommunication Industry.